A vascularized microphysiological system reproducing endochondral ossification in vitro to study ewing sarcoma proliferation and migration - Colombo, Maria Vittoria; Arrigoni, Chiara; Faehling, Tobias; Verrillo, Antonietta; Secci, Viviana; Grünewald, Thomas G. P.; Talò, Giuseppe; Kummer, Alexandra; Gonzalez, Jorge; De Rosa, Vincenzo; Candrian, Christian; Barbero, Andrea; et al. (Advanced functional materials, 2025)
Endochondral ossification (ECO) is the process at the basis of long bone development, occurring in children and involving vascularization and subsequent mineralization of a cartilage template. Deregulated bone developmental pathways could correlate with pediatric bone tumors, including Ewing Sarcoma (EwS), an aggressive tumor with a poor prognosis for patients with recurrent or metastatic disease. Considering the limitations of available EwS preclinical models, at developing a microphysiological system recapitulating bone developmental steps are aimed, to investigate their influence on EwS cell proliferation and migratory behavior. This system includes spheroids of mesenchymal stromal cells sequentially differentiated in chondrogenic and hypertrophic stages within a fibrin hydrogel, in the presence or not of vascular cells and mineralized particles. It shows that by modulating system components it is possible to recapitulate hypertrophic ECO stage, in a higher extent with the addition of vascular cells without a mineral component. Hypertrophic conditions foster the proliferation of EwS cells as compared to avascular and mineralized environments and support the migration of highly aggressive EWSR1::FLI1low cell phenotype, contrarily to empty 3D fibrin gel. Overall, the results support the use of the ECO-mimicking microphysiological system as a valuable preclinical model to investigate the role of developmental mechanisms in EwS onset and progression.